Evaluation of the Content of Ophthalmology Fellowship Program Web sites - Alsaloum, Peter; Alsaloum, Matthew; Kim, Tyler J.; Zheng, David X.; Valentim, Carolina C. S.; Muste, Justin C.; Goshe, Jeffrey M.; Singh, Rishi P. (Journal of Academic Ophthalmology, 2022)
Purpose To assess the availability and content of fellowship program Web sites (FPWs) among ophthalmology subspecialties.Design This is a cross-sectional study.Subjects Web sites of all Association of University Professors of Ophthalmology-accredited fellowship programs in five subspecialties (i.e., surgical retina and vitreous; cornea, external disease, and refractive surgery; glaucoma; neuro-ophthalmology; and pediatric ophthalmology).Methods FPWs were assessed for the presence of 26 key content criteria encompassing program demographics (n = 13), features (n = 10), and social life (n = 3). The presence of each content criterion as well as the content criteria groups were compared across subspecialties.Main Outcome Measures The main outcome measured is the average percentage of key content criteria present among ophthalmology fellowship Web sites.Results Among 266 accredited fellowship programs, 240 (90.2%) had Web sites. On average, Web sites reported 14.9 of 26 key content criteria (57.2%), 8.29 of 13 demographic criteria (63.8%), 5.84 of the 10 program features criteria (58.4%), and 0.705 of the 3 social life criteria (23.5%). Significant differences were identified among subspecialties in the presence of program description (p = 0.046), hospital affiliation (p < 0.001), names of current fellows (p = 0.004), case diversity (p = 0.001), and surgical statistics (p = 0.015). The average number of key criteria differed between subspecialties (p < 0.001).Conclusion There is significant heterogeneity in program fellowship Web site content among ophthalmology subspecialties. Information regarding social life, such as wellness programs and community information, was largely absent across all disciplines. Addressing missing information on ophthalmology FPWs may help optimize program-applicant fit.
Keywords: fellowship; Web site; Web site content; ophthalmology fellowships